The Learning Method Of Gita Buana Soedirman’s Choir Of Jendral Soedirman University Purwokerto - Ardi, Dea Fitri; Raharjo, Eko (Universitas Negeri Semarang, 2021)
Learning methods are ways of presenting subject matter conducted by educators so that the learning process occurs in students in an effort to achieve goals. The problem in this research is how is the method of learning students’ choir Gita Buana Soedirman Purwokerto. This research used the descriptive qualitative method. Data collection is conducted by using observation, interview, and documentation techniques. The data validity technique used is triangulation. Data analysis was conducted in data reduction, data presentation, drawing conclusions, and verification. The results of this study are that in the learning process of the Gita Buana Soedirman Choir’s students apply several learning methods, that are the lecture method, peer tutor method, demonstration method, drill method, and imitation method which are applied continuously and as it should be.